Field report on scaling climate-smart agriculture by kimatwa women sacco in Makindu, Makueni County - Ombati, Bwema; Nzuki, Esther; Waswa, Boaz Shaban; Kinyua, Ivy Wambui (2023)
This field report highlights the progress, challenges, and achievements of the integration of climate-smart agricultural practices by the Kimatwa Women Savings and Credit Cooperative Organization (SACCO) in Makindu, Makueni County.